Novel trypanocide from an extract of Pleurotus sajor-caju against Trypanosoma congolense - Isaiah O. Ademola; Paul O. Odeniran (Taylor & Francis Group, 2017)
Context: Control of African trypanosomiasis relies on chemotherapy, but the development of resistance and the problem of drug residues require research for alternatives. Triterpenes and phenolics, the major constituents of Pleurotus sajor-caju (Fr.) Singer (Pleurotaceae), are reported to be effective against trypanosomiasis. Objective: Trypanocidal effect of whole Pleurotus sajor-caju aqueous extract was investigated in vivo against Trypanosoma congolense. Materials and methods: Mice (25-32 g) were divided into seven groups of six animals. Mice in groups A-F received 2.5 × 104 trypanosomes, while group G was uninfected. Extracts (100-250 mg/kg) were administered intraperitoneally for 5 days to groups A-D while diminazine aceturate (group E) and normal saline (group F) served as positive and negative controls, respectively. Parasitemia, survival time, body weight and haematological parameters were monitored for 60 days post-treatment. Results: Parasitemia decreased significantly (p < 0.01) post-treatment with 200 and 250 mg/kg of the extract and became undetectable by day 16 and 12 post-infection, respectively; the ED50 was 221.5 mg/kg. The packed cell volume (PCV) and the weight of mice treated with 250 mg/kg extract were 46.20 ± 2.6% and 32.05 ± 3.63 g, respectively, which is higher than the group treated with diminazine aceturate. The mean survival time of animals in groups D and E was >60 days, while that of group F was <4 days. Differential leucocyte count on day 68 post-infection in groups C, D and E were not significantly different. Conclusion: Pleurotus sajor-caju therefore could be a potential source of new trypanocidal drugs.